Amplified sinus-P-wave analysis predicts outcomes of cryoballoon ablation in patients with persistent and long-standing persistent atrial fibrillation: A multicentre study - Creta, Antonio; Venier, Sandrine; Tampakis, Konstantinos; Providencia, Rui; Sunny, Juno; Defaye, Pascal; Earley, Mark J.; Finlay, Malcolm; Hunter, Ross J.; Lambiase, Pier D.; Papageorgiou, Nikolaos; Schilling, Richard J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Outcomes of catheter ablation for non-paroxysmal atrial fibrillation (AF) remain suboptimal. Non-invasive stratification of patients based on the presence of atrial cardiomyopathy (ACM) could allow to identify the best responders to pulmonary vein isolation (PVI). Methods Observational multicentre retrospective study in patients undergoing cryoballoon-PVI for non-paroxysmal AF. The duration of amplified P-wave (APW) was measured from a digitally recorded 12-lead electrocardiogram during the procedure. If patients were in AF, direct-current cardioversion was performed to allow APW measurement in sinus rhythm. An APW cut-off of 150 ms was used to identify patients with significant ACM. We assessed freedom from arrhythmia recurrence at long-term follow-up in patients with APW ≥ 150 ms vs. APW < 150 ms. Results We included 295 patients (mean age 62.3 ± 10.6), of whom 193 (65.4%) suffered from persistent AF and the remaining 102 (34.6%) from long-standing persistent AF. One-hundred-forty-two patients (50.2%) experienced arrhythmia recurrence during a mean follow-up of 793 ± 604 days. Patients with APW ≥ 150 ms had a significantly higher recurrence rate post ablation compared to those with APW < 150 ms (57.0% vs. 41.6%; log-rank p < 0.001). On a multivariable Cox-regression analysis, APW≥150 ms was the only independent predictor of arrhythmia recurrence post ablation (HR 2.03 CI95% 1.28–3.21; p = 0.002). Conclusion APW duration predicts arrhythmia recurrence post cryoballoon-PVI in persistent and long-standing persistent AF. An APW cut-off of 150 ms allows to identify patients with significant ACM who have worse outcomes post PVI. Analysis of APW represents an easy, non-invasive and highly reproducible diagnostic tool which allows to identify patients who are the most likely to benefit from PVI-only approach.